Outline, Divergence Times, and Phylogenetic Analyses of Trechisporales (Agaricomycetes, Basidiomycota) - Liu, Zhan-Bo; Wu, Ying-Da; Zhao, Heng; Lian, Ya-Ping; Wang, Ya-Rong; Wang, Chao-Ge; Mao, Wei-Lin; Yuan, Yuan (Frontiers in Microbiology, 2022)
Phylogenetic analyses inferred from the nuc rDNA ITS1-5.8S-ITS2 (ITS) data set and the combined 2-locus data set [5.8S + nuc 28S rDNA (nLSU)] of taxa of Trechisporales around the world show that Sistotremastrum family forms a monophyletic lineage within Trechisporales. Bayesian evolutionary and divergence time analyses on two data sets of 5.8S and nLSU sequences indicate an ancient divergence of Sistotremastrum family from Hydnodontaceae during the Triassic period (224.25 Mya). Sistotremastrum family is characterized by resupinate and thin basidiomata, smooth, verruculose, or odontoid-semiporoid hymenophore, a monomitic hyphal structure, and generative hyphae bearing clamp connections, the presence of cystidia and hyphidia in some species, thin-walled, smooth, inamyloid, and acyanophilous basidiospores. In addition, four new species, namely, Trechispora dentata, Trechispora dimitiella, Trechispora fragilis, and Trechispora laevispora, are described and illustrated. In addition, three new combinations, namely, Brevicellicium daweishanense, Brevicellicium xanthum, and Sertulicium limonadense, are also proposed.